Nonlithographic technique for the production of large area high density gridded field emission sources - Holland, E; Harrison, M; Huang, M; Wilshaw, P (1999)
We report a novel method for the production of high density arrays of gridded microtip field emission electron sources. The microporous structure of Al2O3, formed by anodization of aluminum, is exploited to provide a high density (5 x 10(8) cm(-2)) of sites for:emitter fabrication without the need for individual lithographic patterning of each emitter. The small size of the resultant emitters enables operation with only moderate extraction voltage (20-50 V). Tests of groups of approximate to 200000 emitters have demonstrated emission current densities suitable for display applications. (C) 1999 American Vacuum Society. [S0734-211X(99)00102-X].